EFFECTS OF POPULATION, TECHNOLOGY AND EDUCATION DEPENDENCE ON HUMAN DEVELOPMENT IN INDONESIA DURING THE COVID-19 PERIOD - Wahyuni, Norma Ayu; Nikensari, Sri Indah; Mukhtar, Saparuddin (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the effect of population dependence, technology, and education on human development. Human development in this Research is measured by adjusted per capita expenditure. The research method used in this study is in the form of panel data from 2019 – 2021 in 34 provinces in Indonesia with a descriptive quantitative model. Based on the partial analysis, the population dependency, technology variable has a positive and significant effect on human development by the probability value of smaller than alpha (0.05). While the education variable has a negative and significat effect on human development in Indonesia during the covid-19 period. Simultaneously, all variables have a significant effect on human development, that is shown through R2 of 99.83% and 0.17% and is explained by other variables outside the study.